2019
DOI: 10.1186/s13104-019-4412-z
|View full text |Cite
|
Sign up to set email alerts
|

A real-time PCR screening assay for the universal detection of lumpy skin disease virus DNA

Abstract: Objective The resurgence of lumpy skin disease virus isolates of different genotypic natures abolishes the accuracy of assays that target either vaccine or field strain genome. The aim of the present study was to develop a universal real-time PCR assay using TaqMan chemistry to cover field, vaccine, and recombinant strains of lumpy skin disease virus isolates. Results The PCR assay was designed based on a LSDV044 target region that offers a unique identification locus t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…The final elution was conducted with nuclease-free water. The presence of LSDV DNA was initially confirmed by screening with PCR reported previously [31]. The isolates used in the study are outlined in Table 1.…”
Section: Plos Onementioning
confidence: 99%
“…The final elution was conducted with nuclease-free water. The presence of LSDV DNA was initially confirmed by screening with PCR reported previously [31]. The isolates used in the study are outlined in Table 1.…”
Section: Plos Onementioning
confidence: 99%
“…. Sample extracts were analyzed using real-time PCR for the presence of LSDV DNA, as previously described by Sprygin et al 25 . The fluorogenic probe was labeled at the 5′ end with the FAM reporter dye and with BHQ as a quencher at the 3′ end.…”
Section: Real-time Pcr (Quantitative [Q] Pcr)mentioning
confidence: 99%
“…PCR was performed using a Rotor-Gene Q (Qiagen, Germany) instrument and the following thermal-cycling profile: 95 °C for 10 min, followed by 45 cycles at 95 °C for 15 seconds (s) and 60 °C for 60 s. The final reaction volume was 25 μL containing 10 pmol of each primer, as well as 5 pmol of the probe, 25 mM MgCl 2 , 5 μL 5× PCR Buffer (Promega, USA), 1 μL of 10 pmol dNTPs (Invitrogen, USA), and deionized water to make up the final volume. Samples were tested and results interpreted according to the protocol, as previously described 25 . Table 2.…”
Section: Real-time Pcr (Quantitative [Q] Pcr)mentioning
confidence: 99%
“…Alexander et al (2019) reported the development of a new real-time PCR for the detection of LSD virus (LSDV) field, vaccine and recombinant strains as a follow-up of the finding byKononov et al (2019) of vaccine-like LSDV strains outbreaks in Russia and of a recombined LSDV as reported bySprygin et al (2018).…”
mentioning
confidence: 99%